Stem Cell Therapy for Degenerative Disc Disease. (24th April 2012) - Drazin, Doniel; Rosner, Jack; Avalos, Pablo; Acosta, Frank
Abstract : Low back pain is widely recognized as one of the most prevalent pathologies in the developed world. In the United States, low back pain is the most common health problem for adults under the age of 50, resulting in significant societal and personal costs. While the causes of low back pain are myriad, it has been significantly associated with intervertebral disc (IVD) degeneration. Current first-line therapies for IVD degeneration such as physical therapy and spinal fusion address symptoms, but do not treat the underlying degeneration. The use of tissue engineering to treat IVD degeneration provides an opportunity to correct the pathological process. Novel techniques are currently being investigated and have shown mixed results. One major avenue of investigation has been stem cell injections. Mesenchymal stem cells (MSCs) have shown promise in small animal models, but results in larger vertebrates have been mixed.